Intention to Screen for Hepatitis C Among University Students: Influence of Different Communicative Scenarios - Diotaiuti, Pierluigi; Mancone, Stefania; Falese, Lavinia; Ferrara, Maria; Bellizzi, Fernando; Valente, Giuseppe; Corrado, Stefano; Misiti, Francesco (Frontiers in Psychiatry, 2022)
This study aimed to evaluate the influence of different narrative scenarios regarding students’ intention to undergo diagnostic screening for Hepatitis-C and whether gender identification with characters of the scenario could influence the students’ intention to undergo a medical test. A sample of 600 participants was administered three narrative scenarios with different frames (positive, negative, ambivalent), including two gender options (male and female) for the main character of the story. A statistically significant three-way interaction between Scenario, Gender Identification and Time resulted, F(1, 99) = 6.399, p < 0.01. There were significant simple main effects on the Intention to have a diagnostic test for Hepatitis C for the Scenarios with the protagonist of the same gender as the participant, F(1, 299) = 22.808, p < .025, ηp2= 0.067; and after the administration of the negative scenario, F(1, 199) = 76.305, p < 0.025, ηp2= 0.183. The use of a negative scenario with the same gender character was always more effective than the use of a positive framed scenario, even though there was a high level of knowledge regarding the disease, F(1, 99) = 25.712, p < 0.025, ηp2= 0.189. Personal diagnostic testing was not directly associated with knowledge regarding the infection. The findings of this study can ultimately help policy makers develop communication campaigns adapted to target populations as college students, in order to raise awareness of the risk, promote prevention and behavioural change, and encourage medical screening.